The Shackles of Universal History and the Road Not Taken: 'Ambivalent Possibilities' in Maruyama Masao's Thought. Issue 1 (February 2023) - Kibe, Takashi
Abstract : It seems to be a challenging task for those non-Western scholars who are deeply immersed in European intellectual resources to theorise multiple forms of modernity and deparochialise political theory. What difficulty awaits us in non-Western contexts, when we attempt to throw off these shackles and to open up alternative views of modernity? To address this question, this article attempts to critically examine Maruyama Masao (丸山眞男, 1914–1996), an influential scholar on the history of Japanese political thought, with respect to his view of Japanese modernity, thereby exploring what obstacles await him in pursuing the multiplicity view of modernity and how he actually or potentially overcomes them. In doing so, I develop two arguments. First, Maruyama's move towards multiple modernities remains incomplete because he fails to throw off the shackles of universal history. Second, however, we can identify an alternative way in his own thought that, though not taken by himself, potentially goes beyond universal history towards multiple modernities.